2004
DOI: 10.2169/internalmedicine.43.986
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Skin Reactions after Mosquito Bites and Epstein-Barr Virus Reactivation in a Patient with Mantle Cell Lymphoma

Abstract: We detected Epstein-Barr virus (EBV) reactivation in a patient with mantle cell lymphoma (MCL). The patient, a 53-year-old Japanese man, had been referred to our hospital because of generalized lymphadenopathy, hepatosplenomegaly and lymphocytosis and gave a history of intense skin reactions to mosquito bites. The biopsied lymph node contained a monotonous proliferation of medium-sized lymphocytes with scant cytoplasm and slightly irregular nuclei that were CD5 + , CD20 + and CD23 -. Antibody titers of IgG aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Although rare, the association of insect‐bite‐like eruptions and lymphoproliferative malignancies (especially chronic lymphocytic leukaemia) is well established 27–31 . To the best of our knowledge, this is the first reported case of insect‐bite‐like Wells’ syndrome with a clinicopathological correlation, associated with the development of mantle‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 75%
“…Although rare, the association of insect‐bite‐like eruptions and lymphoproliferative malignancies (especially chronic lymphocytic leukaemia) is well established 27–31 . To the best of our knowledge, this is the first reported case of insect‐bite‐like Wells’ syndrome with a clinicopathological correlation, associated with the development of mantle‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 75%
“…It is seen mostly in the first two decades of life, and some cases are associated with EpsteinBarr virus (EBV) infection and natural killer (NK) cell leukemia/lymphoma (1). Shigekiyo et al reported a mantle cell lymphoma (MCL) patient with HMB, which thus suggested a relationship between EBV and MCL (2). On the other hand, Mori et al reported a patient with HMB who developed MCL, which suggested that HMB might be a pathophysiologic condition with a malignant potential (3).…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4) Although exceptional cases of HMB have been reported in patients with chronic lymphocytic leukemia or mantle cell lymphoma without evidence of an EBV infection, no cases of HMB associated with anaplastic large cell lymphoma (ALCL) have yet been reported. 5 , 6) In this study, we report the first case of HMB associated with ALCL.…”
Section: Introductionmentioning
confidence: 83%
“… 1 , 2 , 3 , 4) However, not all cases of HMB develop into NK cell leukemia/lymphoma. 2 , 5 , 6 , 7 , 8) Shigekiyo et al 5) reported a case of HMB developing into mantle cell lymphoma, and Konuma et al 8) and Seon et al 2) also reported cases of HMB that did not develop into NK/T-cell proliferative diseases. To date, 7 patients with HMB have been reported in Korea, including 3 patients with lymphoid neoplasms such as NK cell lymphoma, Hodgkin's lymphoma-like B-cell lymphoproliferative disorder, and marginal zone B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%